Natural antimicrobials in food safety and quality [ - Chikindas, Michael; Rai, Mahendra (CABI, 2011)
The demands of producing high quality, safe (pathogen-free) food rely increasingly on natural sources of antimicrobials to inhibit food spoilage organisms and foodborne pathogens and toxins. Discovery and development of new antimicrobials from natural surces for a wide range of application requires that knowledge of traditional sources for food antimicrobials is combined with the latest technologies in identification, characterization and application. This book explores some novel, natural sources of antimicrobials as well as the latest developments in using well-known antimicrobials in food.